ANALYSIS OF POTENTIAL PROFILE CHANGES IN THE BRAIN DUE TO NOISE IN HYPERTENSION PATIENTS - Prijo, Tri Anggono; Istiqomah, Istiqomah; Kawitana, Welina Ratnayanti (Universitas Airlangga, 2022)
This study aims to determine the relationship of the potential profile of the brain to noise so that it can affect changes in blood pressure. This research is a type of observational research conducted by treating hypertension and normal blood pressure test. The treatment given was to record brain waves that were given various disturbances of sound intensity levels of 100 dB, 110 dB and 120 dB with a single frequency = 12,000 Hz which was obtained from mosquito noise sources. The recording was done for 60 seconds for each treatment and the data was taken every 2 seconds on the results of the Electroencephalogram (EEG). The analysis used is the FFT test which is generated from the Electroencephalogram (EEG) recording through the program work Labscribeand paired t-test using the SPSS program. The results showed that at varying levels of sound intensity and frequency 12,000 Hz produced theta (hypertension) and alpha (normal blood pressure) brain waves which produced serotonin hormones and caused dilation of blood vessels so that blood pressure decreased. The results of the t-test showed that there was an effect on normal tests on diastole and no effect on systole.